Kids first soccer - Frankl, D.
Soccer is the fastest growing sport for boys and girls in America. The quality of some of the existing soccer programs for children, however, is a source of growing concern. The available research findings on youth sport provide very clear guidelines to better serve children's, as opposed to adults' needs. The purpose of this Web page is to promote a child centered approach to the organization and instruction of youth sports. Special emphasis is placed on the promotion of the game of soccer as a life-long, family oriented activity, that provides for child-parent bonding, team work and friendships, as well as, adequate aerobic exercise. This is a message from a sport psychologist and soccer parent to fellow soccer moms and dads. What's New? Coaching Philosophy Setting Goals Sport Parenting Positive Discipline Soccer Violence Team Dynamics Player Development Skills Assessment Fundamentals Getting Ready Ideas for Practice Lead-up Games Endurance Flexibility Nutritional Principles Safety Tips The Laws of Soccer The Referee Book Reviews Related Links Computing Terms